Epidural Cervical Hematoma in a Whiplash Cervical Injury: A Rare Condition (Medico Legal Update, 2021)
“Whiplash Injury” describes those injury deriving from the sharp whipping movement of both head andneck, produced at the moment of a traffic accident, particularly following collision from behind, head-on orside collisions. The use of safety belts has led to a reduction in deaths deriving from front-end collisions, butalso to an increase in cases of typical whiplash. There are two types of forces that cause whiplash injuries inrear-end car crashes: external forces applied to the body by the seat and head restraint, and internal forcesgenerated by the activation of body’s muscles. The combination of these forces causes differential motion ofthe cervical spine, which results in neck tissues’ strain. This event can affect all neck structures: facet jointscapsule, muscles, intervertebral disks, nerves and vessels. We report a case of a 68-year-old woman. Thesubject, while driving her car, hit head-on a car moving in the opposite direction and died immediately. Atautopsy the major findings were limited to multiple rib fractures and fracture of the fifth cervical vertebrawith epidural hematoma. This case demonstrates that, even in the absence of direct traumatism, a potentiallylethal epidural hematoma may occur as a result of whiplash.